PROCESSING AND ANALYSIS OF DATA OF natural experiment FOR DETERMINING THE tragectory CHARACTERISTICS OF A ROUND PARACHUTE AT HIGH ALTITUDES - S. V. Zhurin; Yu. N. Gvozdev; A. D. Lykov (Научный вестник МГТУ ГА)
The article is devoted to the analysis of the trajectory parameters obtained during the flight experiment at the start of meteo-rocket MMP-06, to determine major parameters of motion of a round parachute at subsonic speeds in the range of altitudes from 0 to 60 km. The Reynolds number is changed in the range from 104 to1,5·106.The main parameters of the trajectory were obtained according to the experimental data. Only laboratory research on a model parachute systems in such a wide range of Reynolds numbers are found in the literature on parachute subjects. This article obtained results of flight experiment.